2020
DOI: 10.1016/j.jjcc.2020.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler indices of diastolic function as prognosticator in patients without heart failure in primary care

Abstract: Background: Tissue Doppler imaging (TDI) indices of left ventricular (LV) diastolic function provide incremental prognostic information on mortality and morbidity in the general population and in several clinical scenarios. Their independent, additional role in outpatients with normal LV ejection fraction (LVEF) and without heart failure (HF) is undefined. Methods: We reviewed clinical and echocardiographic records of 2628 consecutive outpatients 52.8% male, median age 71 years) with LVEF > 50% without concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Given the rising incidence of HFpEF in the elderly population, a need exists for novel, noninvasive diagnostic markers. Prior studies have shown that e′ and E/e′ ratio are not predictive of heart failure in the elderly population, and even within HFpEF, degrees of diastolic dysfunction can vary significantly 3,4 . Diastolic function changes as one ages with slowing of relaxation, decreased diastolic recoil and increase stiffness 5,9,13,22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the rising incidence of HFpEF in the elderly population, a need exists for novel, noninvasive diagnostic markers. Prior studies have shown that e′ and E/e′ ratio are not predictive of heart failure in the elderly population, and even within HFpEF, degrees of diastolic dysfunction can vary significantly 3,4 . Diastolic function changes as one ages with slowing of relaxation, decreased diastolic recoil and increase stiffness 5,9,13,22 .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 e′ declines with normal healthy aging and may be considered abnormal by diastolic dysfunction criteria in over two-thirds of elderly patients. [3][4][5] Better identification of heart failure with preserved ejection fraction (HFpEF) is of particular interest because noninvasive diagnosis is limited, and prevalence is high among seniors. 6 Echocardiographic markers of diastolic dysfunction include sequelae of increased left atrial pressure (E/e′, right ventricular systolic pressure, left atrial (LA) size), which may not be elevated in euvolemic or early stage HFpEF patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a recent cohort of HFrEF, guideline-based diastolic-grading algorithm independently predicted mortality but was undefinable in 30% of subjects implicating a better prognostic performance of elevated E/e′ ratio [ 35 ]. However, in patients with normal LVEF, the relationship of E/e’ with LVFP is modest, and hence, using E/e’ for estimating LVFP in routine clinical practice is of limited benefit [ 36 , 37 ]. We used only un-enhanced TR velocities; thus, we cannot rule out some underestimation of the prevalence of increased estimated pulmonary pressures.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular indices are the left ventricular shortening rate and ejection fraction [10]. With the quick advancement of tissue Doppler technology, strain/strain rate imaging, quantitative tissue velocity imaging, and tissue tracking imaging technologies may now precisely and dependably assess patients' cardiac function [11]. The myocardial function can be locally analyzed and assessed using two-dimensional speckle tracking imaging.…”
Section: Introductionmentioning
confidence: 99%